Antibody-associated epilepsies: Clinical features, evidence for immunotherapies and future research questions. (October 2016) - Bakpa, Ochuko D.; Reuber, Markus; Irani, Sarosh R.
Highlights: ⿢ The field of autoimmune epilepsies has increasing relevance to general epileptology. ⿢ Established clinical features often associate closely with autoantibody specificities. ⿢ The diseases often respond well to early immunotherapies plus rapid escalation. ⿢ Randomized controlled trials are eagerly awaited. Abstract: Purpose: The growing recognition of epilepsies and encephalopathies associated with autoantibodies against surface neuronal proteins (LGI1, NMDAR, CASPR2, GABAB R, and AMPAR) means that epileptologists are increasingly asking questions about mechanisms of antibody-mediated epileptogenesis, and about the use of immunotherapies. This review summarizes clinical and paraclinical observations related to autoimmune epilepsies, examines the current evidence for the effectiveness of immunotherapy, and makes epilepsy-specific recommendations for future research. Method: Systematic literature search with summary and review of the identified publications. Studies describing the clinical characteristics of autoantibody-associated epilepsies and treatments are detailed in tables. Results: Literature describing the clinical manifestations and treatment of autoimmune epilepsies associated with neuronal cell-surface autoantibodies (NSAbs) is largely limited to retrospective case series. We systematically summarize the features of particular interest to epileptologists dividing patients into those with acute or subacute encephalopathies associated with epilepsy, and those with chronic epilepsy without encephalopathy. Available observational studies suggest that immunotherapies are effective in some clinical circumstances but outcome data collection methods require greater standardization. Conclusions: The clinical experience captured suggests that clusters of clinical features associate well with specific NSAbs. Intensive and early immunotherapy is indicated when patients present with autoantibody-associated encephalopathies. It remains unclear how patients with chronic epilepsy and the same autoantibodies should be assessed and treated. Tables in this paper provide a comprehensive resource for systematic descriptions of both clinical features and treatments, and highlight limitations of current studies.